Studying ongoing and spontaneous pain in rodents: challenges and opportunities - Tappe-Theodor, Anke; Kuner, Rohini (European journal of neuroscience, 2014)
The measurement of spontaneous ongoing pain in rodents is a multiplex issue and a subject of extensive and longstanding debate. Considering the need to align available rodent models with clinically relevant forms of pain, it is of prime importance to thoroughly characterize behavioral outcomes in rodents using a portfolio of measurements that are not only stimulus-dependent but also encompass voluntary behavior in unrestrained animals. Moreover, the temporal course and duration of behavioral tests should be taken into consideration when we plan our studies to measure explicit chronic pain, with a particular emphasis on performing longitudinal studies in rodents. While using rodents as model organisms, it is also worth considering their circadian rhythm and the influence of the test conditions on the behavioral results, which are affected by social paradigms, stress and anxiety. In humans, general wellbeing is closely related to pain perception, which also makes it necessary in rodents to consider modulators as well as readouts of overall wellbeing. Optimizing the above parameters in study design and the new developments that are forthcoming to test the affective motivational components of pain hold promise in solving inconsistencies across studies and improving their broad applicability in translational research. In this review, we critically discuss a variety of behavioral tests that have been developed and reported in recent years, attempt to weigh their benefits and potential limitations, and discuss key requirements and challenges that lie ahead in measuring ongoing pain in rodent models.